2022
DOI: 10.2320/matertrans.mt-m2022078
|View full text |Cite
|
Sign up to set email alerts
|

Flux-Free Brazing of Aluminum Alloys under Ultra-Low Oxygen Partial Pressure through a Zirconia Oxygen Pump

Abstract: Flux-free brazing of aluminum alloys was carried out under high purity nitrogen gas with ultra-low oxygen partial pressure prepared by zirconia oxygen pump. The flux-free brazability of the aluminum alloys was improved by adding a small amount of magnesium into the sample, which was more effective in the core alloy than in the brazing filler alloys. Higher heating rate of the sample increased the fillet length. When the oxygen partial pressure of atmospheric gas was much reduced to the order of 10 ¹25 Pa using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Specifically, hydrogen was measured in situ using an oxygen pump sensor containing yttria-stabilized zirconia, which is a solid electrolyte. These measurements showed that even a small amount of hydrogen can be accurately measured [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 90%
“…Specifically, hydrogen was measured in situ using an oxygen pump sensor containing yttria-stabilized zirconia, which is a solid electrolyte. These measurements showed that even a small amount of hydrogen can be accurately measured [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 90%